Relationship between Symptoms of Adenoid Hypertrophy and Adenoidal Nasopharyngeal Ratio in Children at a Tertiary Hospital - Rijal, Anupama Shah; Tuladhar, Abhushan Siddhi; Joshi, Rupesh Raj; Shrestha, Kundan Kumar; Dhungana, Anup; Khadka, Rupak (Nepal Medical College Journal, 2023)
Adenoid hypertrophy (AH) is a common problem in the paediatric age group causing nasal obstruction, snoring, waking up at night, nasal discharge, mouth breathing and decrease in hearing. This causes considerable morbidity in children along with various sequalae. The adenoidal nasopharyngeal ratio (ANR) is an objective method to assess AH and is calculated using a lateral neck x-ray. The study assessed the relationship between symptoms of AH and ANR. A cross-sectional, hospital-based study was conducted in children between the ages of 2 to 14 years. History of the symptoms was obtained and ANR was calculated using a lateral neck x-ray. There was a male preponderance of 1.3:1, with the majority of children between 6 to 10 years of age (67.3%). The common symptoms were nasal discharge (81.1%), mouth breathing (79.8%), snoring (76%) and decrease in hearing (66.3%). The largest mean adenoid size was 18.20 ± 2.63 mm in the 6-10 years, while the greatest mean nasopharyngeal depth was in the 11-14 years old age group (34.50 ± 2.88 mm). The maximum mean ANR of 0.71 ± 0.11 was in the 2-5 years old. All the symptoms of AH showed statistically significanct relationship with high ANR; snoring (p=0.003), waking up at night (p=0.001), nasal discharge (p=0.001), mouth breathing (p=0.034), decrease in hearing (p=0.030). It was seen that the highest number of children affected was in the younger age group where ANR was higher. ANR on nasopharyngeal x-ray (lateral view) correlated well and showed significant relationship with symptoms of AH.